Role for the banana AGAMOUS‐like gene MaMADS7 in regulation of fruit ripening and quality. Issue 3 (22nd June 2015) - Liu, Juhua; Liu, Lin; Li, Yujia; Jia, Caihong; Zhang, Jianbin; Miao, Hongxia; Hu, Wei; Wang, Zhuo; Xu, Biyu; Jin, Zhiqiang
<x xml:space="preserve">Abstract</x> MADS‐box transcription factors play important roles in organ development. In plants, most studies on MADS‐box genes have mainly focused on flower development and only a few concerned fruit development and ripening. A new MADS‐box gene named MaMADS7 was isolated from banana fruit by rapid amplification of cDNA ends (RACE) based on a MADS‐box fragment obtained from a banana suppression subtractive hybridization (SSH) cDNA library. MaMADS7 is an AGAMOUS‐like MADS‐box gene that is preferentially expressed in the ovaries and fruits and in tobacco its protein product localizes to the nucleus. This study found that MaMADS7 expression can be induced by exogenous ethylene. Ectopic expression of MaMADS7 in tomato resulted in broad ripening phenotypes. The expression levels of seven ripening and quality‐related genes, ACO1, ACS2, E4, E8, PG, CNR and PSY1 in MaMADS7 transgenic tomato fruits were greatly increased while the expression of the AG‐like MADS‐box gene TAGL1 was suppressed. Compared with the control, the contents of β‐carotene, lycopene, ascorbic acid and organic acid in transformed tomato fruits were increased, while the contents of glucose and fructose were slightly decreased. MaMADS7 interacted with banana 1‐aminocyclopropane‐1‐carboxylic acid (ACC) oxidase gene 1 (MaACO1) and tomato phytoene synthase gene (LePSY1) promoters. Our results indicated that MaMADS7 plays an important role in initiating endogenous ethylene biosynthesis and fruit ripening.